Intravenous anesthesia with high-flow nasal cannula improves recovery in elderly undergoing ureteroscopic lithotripsy: a prospective controlled study - Lifei Tang; Ran Guo; Yaochen Quan; Haiwen Zhang; Yingcong Qian; Youjia Yu; Shaoyong Song; Jian Li (BMC Anesthesiology)
Abstract Background Intravenous anesthesia with high-flow nasal cannula (HFNC) has been reported to benefit oxygen reserves and enhance postoperative recovery in surgeries requiring low neuromuscular blockade. This study investigated whether HFNC improves recovery quality in elderly undergoing ureteroscopic holmium laser lithotripsy (UHLL). Methods We enrolled 106 elderly patients undergoing UHLL, with 96 patients (48 per group) included in the final analysis. Patients were randomly assigned (1:1, stratified by sex) to receive either HFNC (HFNC group) or laryngeal mask airway (LMA) assisted general anesthesia (LMA group). The primary outcome was the Quality of Recovery 15-questionnaire (QoR-15) scores. Secondary outcomes included PACU stay duration, time to out-of-bed mobilization, length of hospital stay, airway dryness scores, surgeons’ satisfaction, and postoperative complications. Results Compared to the LMA group, the HFNC group achieved significantly higher QoR-15 scores (125.5 [118.3–130.0] vs. 136.5 [126.3–139.0]; difference = -9, 95%CI, -11 to -5; P < 0.001) on the first postoperative day. For secondary outcomes, the HFNC group had a shorter PACU stay (difference = 11.6 min, 95% CI, 10.4–12.8 min), earlier out-of-bed mobilization (difference = 31.8 min, 95% CI, 30.6–33.1 min), lower mouth (difference = 2, 95% CI, 1–3) and throat dryness scores (difference = 2, 95% CI, 1–3) at 30 min post-operation, and lower rates of postoperative sore throat (14.6% vs. 0%; P = 0.019) and cough with sputum (odds ratio [OR] = 9.4, 95% CI, 1.1–78.4). No significant differences were observed between the groups for other measures. Conclusions HFNC can improve recovery quality in elderly patients after UHLL compared to LMA-assisted general anesthesia. Trial registration This trial was registered on July 20, 2023, in the Chinese Clinical Trial Registry (ChiCTR2300073757).